Hypertrophic Obstructive Cardiomyopathy: Comparison of Outcomes After Myectomy or Alcohol Ablation - Meng, Xiangbin; Wang, Wen-yao; Gao, Jun; Zhang, Kuo; Zheng, Jilin; Wang, Jing-jia; Liu, YuPeng; Shao, Chunli; Tang, Yi-Da (Frontiers in Cardiovascular Medicine, 2022)
Introduction and objectives: Patients with HOCM suffer a much higher risk of ventricular arrhythmias and heart failure than the normal population, and accumulating evidence suggests that HOCM is the leading cause of sudden cardiac death in the young. We reported our experience in a comprehensive study comparing surgical myectomy and alcohol septal ablation (ASA). Methods: The original cohort consisted of 965 consecutive patients with HOCM. Patients were divided into three groups according to treatment options: myectomy group (n=502), ASA group (n=138), non-invasive group (n=325). The Median follow-up duration was 42.99±18.32 months, and the primary end-point was a composite of all-cause mortality and cardiac transplantation. Results: Both in short- and long-term observation, surgical myectomy brought much more decrease in LVOT gradient (7 days, 16.15±12.07 mmHg vs. 42.33±27.76 mmHg, p<0.05; 1 year, 14.65±13.18 mmHg vs. 41.17±30.76 mmHg, p<0.05). In univariate Cox survival analysis, both ASA (HR: 0.383, 95%CI: 0.169~0.867, p=0.021) and myectomy (HR: 0.211, 95%CI:0.104~0.429, p<0.001) could bring benefit for long-term prognosis compared with the non-invasive group. We did some subgroup analysis and found some interesting conclusions. Conclusions: In these three groups, patients with myectomy seemed to suffer from the lowest risk of reaching the all-cause mortality and cardiac transplantation end-point. But, in the multivariate Cox survival analysis, we did not fund any difference in end-point events during long-term follow-up during myectomy and ASA. Furthermore, in the age<56years group, myectomy showed significantly associated with all-cause mortality and cardiac transplantation.